First-principles study on the faulted interface of dislocation-sheared T1 precipitates - Ruohan Shen; Xianchang Li; Panwang Zhou (Materials & Design)
The T1 phase is a crucial shearable precipitate that enhances the strength of Al-Cu-Li alloys. Its strengthening effect is associated with the energy of the faulted interfaces generated upon dislocation-shearing of the precipitates. Due to the extremely small size of the T1 phase, this energy cannot be directly measured, and the atomic arrangement around the faulted interface has never been characterized, leading to a knowledge gap regarding these interfaces. This work constructed large-scale supercells that encompassed both precipitate and matrix atoms for a first-principles examination of the faulted interfaces. Two opposite dislocation-shearing actions were incorporated to reserve the overall periodicity of the supercells, which is essential for compatibility with density functional theory calculations. Rigorous statistical analysis of the faulted interface energy was facilitated by modeling a variety of possible atomic arrangements of the faulted interfaces and investigating scenarios with T1 phases of 1, 2, and 3 unit-cells in thickness. Following density functional theory relaxation of the supercells, the results demonstrated satisfactory convergence. The faulted interface energy was calculated as approximately 4 to 5 times the unstable stacking-fault energy of the matrix. The diverse thickening mechanisms of T1 precipitates were found to significantly alter the overall FIE of the thickened precipitate.